2016
DOI: 10.1016/j.jvs.2015.08.086
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin nanoparticles inhibit stent thrombosis in ex vivo static and flow models

Abstract: Introduction Despite significant advances in intravascular stent technology, safe prevention of stent thrombosis over prolonged periods after initial deployment persists as a medical need to reduce device failure. The objective of this project was to assess the potential of perfluorocarbon nanoparticles conjugated with the direct thrombin inhibitor D-phenylalanyl-L-prolyl-L-arginyl chloromethylketone (PPACK-NP) to inhibit stent thrombosis. Methods In a static model of stent thrombosis, 3 mm × 3 mm pieces of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Development of materials with low propensity to cause contact activation would reduce the risk of device-associated thrombosis 63 . Similar to nanoparticle drug-eluting stents coupled with a direct thrombin inhibitor 64 , targeting procoagulant polyP by PPX immobilized on catheters, stents or artificial heart valves could provide a safe novel approach of anticoagulation that can be employed in FXII-related disease states. Furthermore, the enzymatic activity of PPX would facilitate degradation of multiple polyP molecules, potentially exceeding the antithrombotic activity of currently used anticoagulants such as thrombin and FXa inhibitors that target a single coagulation protease.…”
Section: Discussionmentioning
confidence: 99%
“…Development of materials with low propensity to cause contact activation would reduce the risk of device-associated thrombosis 63 . Similar to nanoparticle drug-eluting stents coupled with a direct thrombin inhibitor 64 , targeting procoagulant polyP by PPX immobilized on catheters, stents or artificial heart valves could provide a safe novel approach of anticoagulation that can be employed in FXII-related disease states. Furthermore, the enzymatic activity of PPX would facilitate degradation of multiple polyP molecules, potentially exceeding the antithrombotic activity of currently used anticoagulants such as thrombin and FXa inhibitors that target a single coagulation protease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PPACK nanoparticles could specifically bind to acute thrombotic lesions and enable detection of the thrombus by MRI. In a follow-up study, Palekar et al [89,90] found that with the accumulation of thrombin in the coronary stent, PPACK nanoparticles continuously bound to and inactivated thrombin molecules on the surface, forming an "anti-coagulation" surface. Results showed that these PPACK perfluorocarbon nanoparticles were also able to prevent the formation of coronary stent thrombosis.…”
Section: Theranostic Nanoparticles For Thrombosismentioning
confidence: 99%
“…Nanoparticles and nanomedicines contribute to various pharmaceutical applications, like diagnosis of disease progression, drug delivery, and treatment of various ailments, such as cancer, thrombosis, wounds, osteoporosis, vertebral fracture, and microbial infective diseases, e.g., TB and HIV-associated opportunistic infections (Khajuria et al, 2014;Palekar et al, 2016;Sagar et al, 2015;Tang et al, 2015;Wolfram et al, 2015). Furthermore, it is expected that they will produce potential therapeutic agents for neuroinfective disorders.…”
Section: The Mechanistic Approach Of Nanomedicine For Neuroinfectiousmentioning
confidence: 99%